Comparative analysis of knowledge bases: system architecture - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 2023)
When comparing similar knowledge bases the question arises: what situations produce different conclusions in these bases? The task of comparing knowledge bases can emerge in different domains. For example, in legal domain, it is sometimes essential to compare different versions of a legal act or similar legal acts of different countries. The article presents an architecture of the system designed for the automated comparing of knowledge bases. The architecture implements the method of comparing based on the construction of elementary test situations.